2016
DOI: 10.1126/scitranslmed.aad0015
|View full text |Cite
|
Sign up to set email alerts
|

USF1 deficiency activates brown adipose tissue and improves cardiometabolic health

Abstract: USF1 (upstream stimulatory factor 1) is a transcription factor associated with familial combined hyperlipidemia and coronary artery disease in humans. However, whether USF1 is beneficial or detrimental to cardiometabolic health has not been addressed. By inactivating USF1 in mice, we demonstrate protection against diet-induced dyslipidemia, obesity, insulin resistance, hepatic steatosis, and atherosclerosis. The favorable plasma lipid profile, including increased high-density lipoprotein cholesterol and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 55 publications
3
75
0
Order By: Relevance
“…Changes in thermogenesis are known to affect metabolic responses in animals and humans 19, 46, 47 . Therefore, we next examined glucose tolerance in Ldlr −/− and Apoe −/− mice fed a cholesterol-enriched diet housed at 22°C and 30°C ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in thermogenesis are known to affect metabolic responses in animals and humans 19, 46, 47 . Therefore, we next examined glucose tolerance in Ldlr −/− and Apoe −/− mice fed a cholesterol-enriched diet housed at 22°C and 30°C ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Laurila et al demonstrated that lacking upstream stimulatory factor 1 (USF1) activated BAT in obese/T2DM mice, and promoted protection against dyslipidaemia, obesity, insulin resistance, and atherosclerosis. These data were also confirmed in subjects carrying a mutation in USF1 [82]. Also, steroid glycosides as ginsenoside Rb1 improved glucose and lipid metabolisms and reduced body weight in obese animals by up-regulating PRDM-16, PGC1α, and UCP-1 expression and WAT browning [83].…”
Section: Anti-obesity Strategies and Reduction Of Cardiovascular Riskmentioning
confidence: 81%
“…Interestingly, high-fat diets stimulated browning capacity of WAT in the retroperitoneal depot by stimulating UCP-1 and CIDE-A (cell death-inducing DFFA-like effector-A) expression, likely, as a compensation mechanism [81]. Also, micro-RNAs such as miR-26, miR-27, mir-30, miR-34a, miR-106b, miR-133, miR-155, miR-193-365, miR-196 and miR-378 have been involved in the control of bAT and BAT formation and function in mice [82]. …”
Section: Anti-obesity Strategies and Reduction Of Cardiovascular Riskmentioning
confidence: 99%
“…Findings from mouse models demonstrate that cold-activated BAT can effectively clear plasma triglycerides [4850] and may even mitigate hypercholesterinemia and suppress the formation of atherosclerotic plaque [51, 52, 49]. One study demonstrated a retardation of atherosclerotic plaque growth with only 8 weeks of cold exposure [53]; however, this may have been the result of rapid exposure instead of gradual acclimation.…”
Section: Contributions Of Bat To Energy Metabolism Glucose Metabolismentioning
confidence: 99%